(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe preoperative anxiety and identify some associated factors among emergency surgery patients at the Emergency Department of Thien Hanh General Hospital Methods: A cross-sectional study was conducted on 420 patients, who were directly interviewed using a structured questionnaire. Anxiety level was assessed using the Hospital Anxiety and Depression Scale – Anxiety (HADS-A). Data were analyzed using SPSS version 20.0. The Chi-square test was used to determine the differences in preoperative anxiety levels in relation to various variables. Results: The findings revealed a high prevalence of preoperative anxiety (82.4%). Specifically, mild anxiety accounted for 38.6%, moderate anxiety 20.7%, and severe anxiety 23.1%. The issue causing the most anxiety among patients was postoperative pain (51.9%). Statistically significant factors associated with preoperative anxiety included gender, history of chronic illness, history of previous surgeries, and type of current surgery (p<0.05). Conclusion: Patients awaiting emergency surgery exhibited a notably high rate of anxiety. Higher anxiety levels were observed among female patients, those without chronic medical conditions, individuals with no history of previous surgeries, and those undergoing orthopedic trauma procedures. These findings highlight the need for early psychological assessment and targeted interventions to manage anxiety in high-risk groups, particularly in emergency surgical settings.